Foreword - B. Bradford (Kansas Agricultural Experiment Station Research Reports, 2017)
Kansas State University is pleased to present the 2017 Dairy Research Report of Progress. We continue to watch the Kansas dairy industry grow, and in 2016 our state ranked 10th for largest growth in total milk produced. During the past 5 years (2011 to 2016), total milk production in Kansas has increased by 29%; the number of cows by 18%; and annual pounds of milk per cow by 1,785. Therefore, the Kansas dairy herd is not only growing, but is becoming more productive and efficient. At the end of 2016, Kansas ranked 13th nationally in milk yield per cow at 22,801 lb, 16th in the number of dairy cows (146,000), and 16th in total milk production (3.33 billion lb). Kansas now has 290 dairy operations and averages 503 cows per herd (Hoard’s Dairyman, March 25, 2017, pp 204–205).
Keywords: Dairy cattle